Indonesian Rainforest Plants - Chemodiversity and Bioactivity - S.A, Achmad,; E.H, Hakim,; L.D, Juliawaty,; L, Makmur; Maolana, yah, Y. (Malaysian Journal of Science, 2005)
Discovery of natural products for pharmaceutical and agrochemical industries is in rapid development during the last decades. This increased interest is primarily due to the diversity of chemical structures found in nature, and it can be expected that these natural compounds will become more important in bioindustries. To date only a small percentage of the living organisms in the biosphere have been described, and there exists an enormous and still undiscovered natural compounds of obviously unlimited structural diversity, particularly in the tropical rain forests. This paper will present the recent status of part of our works on natural products derived from the Indonesian rain forest plants, covering substantial structural diversity and biological activity, from a number of species of Artocarpus (Fam. Moraceae) largely distributed in Indonesia.